Faktor Penentu Alih Fungsi Lahan Sawah di Tingkat Rumah Tangga Petani dan Wilayah di Provinsi Bali - Putri, Nawang (Program Studi Ekonomi Syariah STAI Senori Tuban, 2025)
The conversion of rice fields to non-agricultural uses in Bali poses a serious threat to food security and the sustainability of the Subak traditional irrigation institution. This study aims to identify the driving factors behind rice field conversion at both the regional and household levels. A quantitative approach was employed using a survey method. Secondary data were obtained through a literature review from various relevant sources. Data analysis was conducted using two approaches: (1) logistic regression to examine the factors influencing farmers’ decisions to convert their rice fields at the household level, and (2) multiple linear regression with the Ordinary Least Squares (OLS) method to analyze the determinants of land conversion rates at the regional level. The results show that, at the household level, land conversion is influenced by land sale value, rice productivity, land tax, the proportion of income derived from rice farming, damaged irrigation infrastructure, and proximity to main roads. At the regional level, the conversion rate is significantly affected by the growth of non-agricultural Gross Regional Domestic Product (GRDP), rice production, population size, the number of hotels and accommodations, and the Farmers’ Terms of Trade (FTT). Spatial planning regulations (RTRW) were found to have no significant effect. These findings highlight the need for more adaptive and context-specific policy approaches to effectively control rice field conversion in Bali.